(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2013)
In this paper, a comprehensive numerical study is presented for the fully developed thermal flows through a rotating curved duct with square cross section. Numerical calculations are carried out over a wide range of the Taulor number 0?Tr?3000 for two cases of the Dean numbers, Dn=1000 and Dn=2000. A tempature difference is applied across the vertical sidewalls for the Grushof number Gr=500, where the outer wall is heated and the inner wall colled. Spectral method is used as a basic tool to slove the system of non-linear differential equations. The rotation of the duct about the center of curvature is imposed, and the effects of rotation (Coriolis force) on the flow characteristics are investigated. As a result, multiple branches of asymmetric stady solutions with two-, three- and four-vortex solutions are obtained. Linear stability of the steady solutions is also investigated. DOI: http://dx.doi.org/10.3329/bjsir.v48i1.15415 Bangladesh J. Sci. Ind. Res. 48(1), 59-70, 2013